(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
The fast-developing technical world and the shift in expectations of the new workforce entering the job market pose new challenges for third level education. Cooperative work and teamwork are now an essential part of every aspect of production. The answer to this new challenge can be the introduction of cooperative learning as a learning method in higher education. Cooperative learning – with sufficient preparation - can be a tool not only to improve the efficiency of the learning process, but at the same time it can help develop competencies and skills that are necessary for higher level students becoming successful in their future career. This study provides an overview of the practice of cooperative learning internationally and it focuses on its pros and possible cons.